Barriers impacting organizational immunization policy implementation in U.S. and Canadian summer camps. Issue 2 (3rd April 2021) - Garst, Barry; Dubin, Alexsandra; Bunke, Carissa; Schellpfeffer, Natalie; Gaslin, Tracey; Ambrose, Michael; Hashikawa, Andrew
ABSTRACT: While immunization practice guidelines for children have been applied within primary schools, little research exists about how immunization practice guidelines are applied within summer camp settings and barriers to policy implementation within those settings. To identify perceived barriers to effective immunization policy implementation in summer camps, data were collected from a purposeful sample of 925 unique summer camp representatives using the CampDoc.com online electronic health record system. Fifty-nine percent (n = 541) of the sample completed an open-ended question about immunization policy barriers, including directors (38%, n = 205), nurses (26%, n = 140), other (20%, n = 106), office staff (13%, n = 73), and physicians (3%, n = 17). Inductive analyses and coder triangulation were used to develop themes. Constructed themes included a lack of parental support for vaccination, difficulties collecting and verifying immunization documentation, variable immunization policy guidelines, immunization exemptions, and organizational focus on financial outcomes. In addition, one-fifth of responding camps perceive no barriers. Camp administrators should work with pediatricians to implement clear and consistent immunization policies emphasizing parent education and informed by local and state guidelines.